charline-picon.com->Distributive-associative-commutative-properties-> SOLUTION: x^2+10=0 this is deal with by factoring, and also the second problem is 2x6^2-3x-2=0 f(x)= 2x^2-7x+3 find f(2).Can you please occupational the troubles out for this reason that ns see how to job-related them out so var visible_logon_form_ = false;Log in or register.Username: Password: register in one simple step!.Reset your password if friend forgot it."; return false; } "> log in On


You are watching: X^2-10 factored

Click below to view ALL difficulties on Distributive-associative-commutative-propertiesQuestion 162786: x^2+10=0 this is fix by factoring, and also the second problem is 2x6^2-3x-2=0 f(x)= 2x^2-7x+3 find f(2).Can you please occupational the difficulties out so that ns see just how to occupational them out so I can do various other problems. Thank you. Discovered 2 remedies by eperette, gonzo:Answer by eperette(173)
*
(Show Source): You deserve to put this equipment on her website! answer by gonzo(654)
*
(Show Source): You have the right to put this systems on your website! some formulas:-----general kind for a quadratic equation is -----general type for the quadratic formula is and also -----general form for the components of a quadratic equation space -----it doesn"t appear that the very first equation will provide real solutions.-----x^2 + 10 = 0x^2 = -10x = +/- sqrt(-10)looks like the answer will certainly not be a genuine number.looking in ~ the general form of a quadratic equation, it looks likea = 1, b = 0, c = 10 because that the equation x^2 + 10 = 0.using the component of the quadratic formula under the square root, becomes i do not care which indicates no actual solution.not sure what you got however if the solution has to be real, there is no solution for the first one.-----i don"t understand your 2nd problem.2x6^2-3x-2 doesn"t do sense.-----if it"s 2x^2-3x-2, then us can uncover a solution.-----here"s just how i would perform it.-----i would look at 2x^2-3x-2 and note the following:a = 2b = -3c = -2-----since c is negative, my equipment will look prefer (x-something) * (x+something)-----what factors will permit me to get c = -2?possible factors are -1, 1, -2, 2.-----what components will allow me to gain a = 2?possible components are 1, 2.-----now i require combinations that a factors and c factors that will add up come -3my feasible factors space -1, 1, -2, 2 because that c, and 1, 2 for a.-----1 - 4 = -3 looks choose it"s the only possible mix that would perform it.i would acquire -4 by multiply -2 * 2i would gain 1 by multiply 1 * 1-----first a meaning of FOIL.FOIL method First, Outer, Inner, Last.it means multiply your an initial terms together first, climate your outer terms with each other next, then your inner terms with each other next, then your last terms next. Add them all up and also you get your equation.-----if your determinants are (a1x + c1) * (a2x + c2), thenF = an initial = a1x * a2x.O = external = a1x * c2I = within = a2x * c1L = last = c1 * c2-----add them increase together and also you geta1x*a2x + a1x*c2 + a2x*c1 + c1*c2 = 0-----one of the Inner components has to it is in -4, and the other one has to be 1.-----in order because that an inner or outer element to be -4, i require (2*x * -2)in order for an inner or outer factor to be 1, i require (x * 1)factors of (2*x + 1) * (x - 2) must do it.inner components are 1*x = 1xouter determinants are 2*x*-2 = -4*x = -4x-4x + x = -3x-----factors look choose they are (2*x + 1) * (x - 2)-----using FOIL, that amounts to 2x^2 + x - 4x -2 = 2x^2 -3x -2 i m sorry is good.-----solution is (2*x+1) * (x-2) = 0.x = -1/2 or x = 2.one or both could work.

See more: What Does Eu Te Amo Mean Ing Of 'Te Amo'? I Love You: Is It Eu Te Amo Or Eu Amo Voce

At least one has to work or the solution is no good.-----substituting x = 2 in the initial equation gets2*2^2 - 3*2 - 2 = 8 - 6 - 2 = 0x = 2 works.-----substituting x = -1/2 in the initial equation gets2*(-1/2)^2 - 3*(-1/2) - 2 = 0 i m sorry becomes2*(1/4) - 3*(-1/2) - 2 = 0multiply both political parties of the equation through 4 to eliminate the denominators and also the equation becomes2 - (-3*2) - 8 = 02 - (-6) - 8 = 02 + 6 - 8 = 0x = -1/2 functions also.-----if girlfriend can"t point out the solution right away, then walk to the quadratic formula. That will administer you through the solution, if there is one.-----general form for a quadratic equation is -----general type for the quadratic formula is and also -----since your equation is 2^x^2 - 3*x -2a = 2b = -3c = -2just substitute these worths in the quadratic formula and solve.-----your last inquiry is to discover f(2) native the equation-----this is just a matter of substititon.you replace x v 2 and solve the equation.the equation becomes2*2^2 - 7*2 + 3which becomes2*4 - 14 + 3which i do not care 8 - 14 + 3which becomes-3f(2) = -3-----
*